Determinants of financial wellness among workers in Jabatan Penyiaran Negeri Sembilan / Rahayu Arshad - Arshad, Rahayu (2012)
The purpose of this study was to examine determinants that influence financial wellness. The results of this study can be used for better understanding on the relationships between and among determinants of financial wellness by highlighting the relationship among financial knowledge, financial behavior, and financial wellness. In this study, the workers in Jabatan personally distributed the questionnaire to 500 respondents. The data obtained from the sample will be analyzed using SPSS method which is primary data. The gathered data from the research process will go through several analyses; hence the result of this study will be interpreted. This study will be analyzed based on frequency analysis, reliability analysis, correlation analysis, and regression analysis. From the researcher findings, all the independent variables (financial knowledge and financial behavior) had significant relationship with dependent variables (financial wellness). This result show that the independent variables positive correlated with dependent variables. The most significant variable is financial behavior where the correlation analysis between financial behavior and financial wellness is the highest.